Dynamics and thermal analysis of the auxiliary bearing for the helium circulator of HTR-PM. (February 2018) - Zhao, Yulan; Yang, Guojun; Liu, Xingnan; Shi, Zhengang; Zhao, Lei; Zhang, Zuoyi
Highlights: The first bending critical frequency of the rotor is provided to support the rigid body assumption. The reason why Lundberg-Palmgren equation is applied in the rotor drop process is explained. The difference of the rotor orbits between the experiment and the simulation is explained. Abstract: The high-temperature gas-cooled reactor-pebble bed module (HTR-PM) has been proposed by the Institute of Nuclear and New Energy Technology of Tsinghua University. The helium circulator is equipped in the primary loop of HTR-PM to drive high-temperature helium for energy exchange. The active magnetic bearing (AMB), replaced by the ordinary mechanical bearing, is chosen as the perfect supporting scheme for the helium circulator of HTR-PM. Additionally, the auxiliary bearing is applied in case of AMB failures and has become indispensable to provide mechanical supports and displacement constraints for the rotor. When the rotor drops down, the auxiliary bearing needs to sustain fierce impacts and corresponding thermal growth. While due to the special environment in the primary loop of HTR-PM, oil or grease lubrication can't be applied in the auxiliary bearing. A new design of unlubricated auxiliary bearing is proposed in this paper. This paper mainly deals with the following two aspects to reveal the rotor drop: dynamic analysis including fatigue life prediction, and corresponding thermal growth. Moreover, dropping experiments are carried out in the HTR-PM helium circulator system. The experimental results can verify the auxiliary bearing capacity to endure the dynamic impact of the dropping rotor, and provide suggestions for the auxiliary bearing type selection. The results in this paper will provide theoretical suggestions for further engineering design and application of the auxiliary bearing in the helium circulator of HTR-PM.